Blood Lead Level Is Negatively Associated With Bone Mineral Density in U.S. Children and Adolescents Aged 8-19 Years - Cui, Aiyong; Xiao, Peilun; Hu, Baoliang; Ma, Yuzhuo; Fan, Zhiqiang; Wang, Hu; Zhou, Fengjin; Zhuang, Yan (Frontiers in Endocrinology, 2022)
Abstract Context: The relationship of lead exposure with bone health in children and adolescents remains controversial. Objection: We aim to investigate the association of blood lead levels (BLL) with bone mineral density (BMD) in American children and adolescents using data from the National Health and Nutrition Examination Survey (NHANES), 2005-2010. Methods: We analyzed 5,583 subjects aged 8-19 years (mean age, 13.49 ± 3.35 years) from the NHANES 2005-2010. BLL was tested using inductively coupled plasma mass spectrometry. BMD was measured by dual-energy X-ray absorptiometry (DXA) at the lumbar spine, total femur, and femur neck. Multivariate linear regression models were used to explore the association between BLL and BMD, adjusting for age, gender, race/ethnicity, poverty income ratio (PIR), body mass index (BMI), serum calcium, and serum phosphorus. Results: BLL is negatively correlated with BMD at different sites of interest in children and adolescents. For every 1mg/dl increase in BLL, the BMD of the total spine, total hip, and femoral neck decreased by 0.011 g/cm2, 0.008 g/cm2, and 0.006 g/cm2. In addition, lead (Pb) affects the lumbar spine more than the femur. The effect estimates are stronger in girls than boys at the lumbar spine (P for interaction= 0.006). This negative association remains significant in American children and adolescents after excluding individuals with BLL more than 3.5 ug/dl. Conclusion: Our study indicates that BLL is negatively correlated with BMD at different sites of interest in children and adolescents aged 8-19 years, even in the reference range. More research is needed to elucidate the relationships between Pb and bone health in children and adolescents, including specific mechanisms and confounding factors like race/ethnicity, gender, and age.